THE REPORT OF SUCCESSFUL THROMBECTOMY FROM BRANCHES OF PULMONARY ARTERY AND RIGHT VENTRICLE WITH CAVA FILTER IMPLANTATION IN PATIENT WITH ANTIPHOSPHOLIPID SYNDROME - V. T. Selivanenko; M. A. Martakov; B. V. Ivashkin; A. V. Vaschenko; V. P. Pronina; V. A. Dudakov; E. M. Zainetdinov (Неотложная медицинская помощь)
Abstract. A rare case of right ventricle and pulmonary artery thrombosis in patient with antiphospholipid syndrome is described. Surgery stages and postoperative management have been demonstrated. It’s a matter of grate importance to unify the efforts of rheumotologists, cardiovascular surgeons, immunologists and detoxication specialists in order to determine an adequate treatment of antiphospholipid syndrome.